The Misericórdias as Social Economy Entities in Portugal and Spain - Antonio José Macías Ruano; José Ramos Pires Manso; Jaime de Pablo Valenciano; María Esther Marruecos Rumí (Religions, 2020)
Las Santas Casas de Misericórdias (The Holy Houses of Mercy) are institutions of Portuguese origin that emerged in the late fifteenth century and that, over time, have expanded beyond the territories of the Portuguese Empire, including to Spain, where various Casas de Misericordia were created in their image and with similar purposes to the original. The Misericórdias continue to be relevant and present throughout Portugal, in various decolonized countries of the former Portuguese Empire, and in other territories that have been influenced by Portuguese emigration, and have always played an important role in the social care of citizens. In Spain, the Santas Casas de Misericordia do not have the same long history, nor the same social relevance as their Portuguese counterparts. However, even today, there are some Casas de Misericordia in Spain that provide social care services, having adopted various legal structures such as foundations, associations, and public entities.